Clinical and pathological characteristics of primary focal segmental glomerulosclerosis in adult - Al-Mukhtar, Safa Ezzidin; Wadee, Salam Fareed (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Focal segmental glomerulosclerosis shares overlapping patterns of injury with segmental consolidation and obliteration of glomerular architecture by the accumulation of collagenous extracellular matrix or by increased cellularity or both. This study aimed to investigate the patterns of primary focal segmental glomerulosclerosis in adults in Erbil. The specific objectives of this study included determining the frequency of histological variant of Focal segmental glomerulosclerosis, defining the clinical characteristics of the primary type in general and recognizing the clinical and pathological characteristics for each variant separately. Methods: A cross-sectional, clinico-pathologic study was conducted for 50 patients attending the Nephrology Department in Erbil Teaching Hospital between March and December 2013. This study included patients of >16 years old with biopsy-proven idiopathic focal segmental glomerulosclerosis. Results: A total of 50 patients were enrolled into this study. The median age of patients was 33 years, ranged from 18 to 54, 31 (62%) males and 19 (38%) females. The frequency of histopathological variants was 80% not otherwise specific focal segmental glomerulosclerosis, 14% glomerular tip lesion, and 6% cellular type. Nephrotic syndrome and hypertension were the main presenting features (92% and 68%, respectively). The mean percentage of sclerosed glomeruli was 40% and the mean interstitial fibrosis and tubular atrophy was 24%. Conclusion: A not otherwise specific variant is a common morphological lesion in many glomerular and non-glomerular diseases, and it is just like a junk drawer of multiple glomerular alterations with this common pattern of the lesion.